DEFENSE MECHANISM IN THOMAS HARDY'S THE MAYOR OF CASTERBRIDGE: A PSYCHOANALYTIC APPROACH - ISWATI , PUJI ASRI (2007)
The major problems of this study are to reveal how the major cha racter's defense mechanism is reflected in Thomas Hardy's The Mayor of Casterbridge based on its structural elements and to analyze the novel base on the psychoanalytic analysis. In analyzing The Mayor of Casterbridge, the writer uses qualitative method. The object ive of the study is Thomas Hardy's The Mayor of Casterbridge in 1986. The data sources are primary data and secondary data source. The primary data source is the novel The Mayor of Casterbridge itself and the secondary data source are the biography of the author, website in the internet about the novel The Mayor of Casterbridge and other resources that support to analysis. The method of data analysis is library research. The outcome of the study shows that the problem faced by the major character causes the conflict of his mental condition. It brings him to defense mechanism which influences his personality. Finally, the change of personality makes him suffering in the end.